2009
DOI: 10.1002/adsc.200900362
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Organic Frameworks (MOFs) as Heterogeneous Catalysts for the Chemoselective Reduction of Carbon‐Carbon Multiple Bonds with Hydrazine

Abstract: The as-synthesized metal-organic frameworks (MOFs), particularly that based on aluminium coordinated with benzenedicarboxylic acid, constitute selective catalysts for the reduction of carbon-carbon multiple bonds in alkenes, alkynes and a,b-unsaturated esters with hydrazine hydrate in acetonitrile under mild conditions. The present protocol enjoys advantages such as convenient reaction conditions and benign, reusable and cost effective catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 43 publications
1
44
0
Order By: Relevance
“…[10] In other words, a material could promote reduction by hydrazine and be inactive for activation of hydrogen gas, as it has been reported for instance for MIL-53(Al), a metal organic framework able to activate hydrazine for multiple carbon-carbon bond reduction. [24] Thus, the outcome of the present study cannot be directly predicted from the results reported so far with CNTs as hydrazine hydrogenation promoter, activation of molecular hydrogen being more challenging owing to the strength of the HÀH bond and of more general applicability.…”
mentioning
confidence: 78%
“…[10] In other words, a material could promote reduction by hydrazine and be inactive for activation of hydrogen gas, as it has been reported for instance for MIL-53(Al), a metal organic framework able to activate hydrazine for multiple carbon-carbon bond reduction. [24] Thus, the outcome of the present study cannot be directly predicted from the results reported so far with CNTs as hydrazine hydrogenation promoter, activation of molecular hydrogen being more challenging owing to the strength of the HÀH bond and of more general applicability.…”
mentioning
confidence: 78%
“…Considering the high metal content in MOFs and its similarity with zeolites, these materials are attracting an increasing interest as heterogeneous catalysts. [16][17][18][19][20][21][22][23][24][25][26][27][28] Table 1 provides a comparison of some features that are relevant in catalysis for zeolites and MOFs. Plays an important role in many reactions…”
Section: Mofs Versus Zeolitesmentioning
confidence: 99%
“…Precedents in the literature based on the product distribution observed for the rearrangement of cyclic acetal of 2-bromopropiophenone [5] have shown that Cu 3 A C H T U N G T R E N N U N G (BTC) 2 can behave as a soft Lewis acid catalyst Also, more recently, we have shown that Cu 3 A C H T U N G T R E N N U N G (BTC) 2 is a suitable heterogeneous catalyst for oxidation of benzylic compounds using tert-butyl hydroperoxide [7] and N-methylation of amines using dimethyl carbonate. [8] Considering that the use of MOFs as heterogeneous catalyst [8][9][10][11] is an area of much current interest it is still necessary to expand the reaction types that can be catalyzed by MOFs trying to delineate the advantages and limitations of these materials as catalysts, particularly versus other common solid catalysts such as zeolite and clays.…”
Section: Introductionmentioning
confidence: 99%